Depressive Symptoms, Anxiety, and Quality of Life in Hemodialysis Patients and Their Caregivers: A Dyadic Analysis. (19th April 2021) - A. Khalil, Amani; Khalifeh, Anas H.; Al‐Rawashdeh, Sami; Darawad, Muhammad; Abed, Mona
Abstract: The current study aimed to examine the effect of depressive and anxiety symptoms on physical and psychological quality of life (QOL) in end‐stage renal disease patient‐family caregiver dyads using the Actor‐Partner Interdependence Model. This was a descriptive cross‐sectional study. Dyads' ( N = 120) symptoms of anxiety and depression and QOL were assessed via the Hospital Anxiety and Depression Scale and the World Health Organization (WHO)QOL‐BREF, respectively. The depression scores were higher (worse) in patients than in caregivers (8.74 ± 5.23 vs. 6.9 ± 3.9, t [ df 119] = 3.339, p = .001). Patients had lower (worse) scores on the physical domain of QOL than the caregivers (47.37 ± 22.9 vs. 64.1 ± 17.49, t [ df 119] = −7.165, p < .001). Anxiety and depressive symptoms exhibited actor effects on the physical and psychological QOL of the dyad. Only depressive symptoms in caregivers exhibited a partner effect on the psychological domain of QOL in patients (β = −.745, p < .05). In conclusion, anxiety and depressive symptoms in both patients and caretakers are equally crucial in end‐stage renal disease management.